Quick response manufacturing and ergonomic consequences in manufacturing environment - Nelfiyanti, .; N. M. Zuki, N. M. (IOP Publishing, 2020)
Many methods can be used in manufacturing industries to minimize the wastage. Waste occurred when the output was below the production target and the high rejection rate of the products due to quality issues. One of the reasons is because of the wrong way of working set-up. Inappropriate working environment can cause workers to feel grievances on their limbs with the frequent complaints are fatigue and musculoskeletal. With this complaint, it has an impact on the smooth production process. Many Methods can be used to minimize waste in the manufacturing industry. One of the methods that can be used is Quick Response Manufacturing (QRM) embedded with ergonomics for the work process. Implementation of the QRM and ergonomic methods in manufacturing companies in different countries is still experiencing some constraints. Therefore, this article contains an analysis to identify and evaluate the application of QRM and ergonomics in the Manufacturing industry based on published articles. The approach can be used to assist in formulating the right model in evaluating the strategies for QRM and ergonomic application in the manufacturing sectors.